Watching the watchers: conducting ethnographic research on covert police investigation in the United Kingdom. (December 2016) - Mac Giollabhuí, Shane; Goold, Benjamin; Loftus, Bethan
It has long been claimed that the police are the most visible symbol of the criminal justice system (Bittner, 1974). There is, however, a significant strand of policing – covert investigation that relies routinely on methods of deception – that resists public revelation (Ross, 2008). The growing importance of covert police investigation has profound implications for the relationship between citizen and the state in a democratic society, but it is relatively unexplored by police researchers. In this article, we describe the methodology of the first ethnographic study of how the introduction of the Regulation of Investigatory Powers Act (2000) – a piece of 'enabling' legislation that regulates the conditions under which law enforcement agencies can intervene in the privacy of individuals – has effected the conduct of covert police investigation in the United Kingdom. We describe our ethnographic experience in the 'secret world' of covert policing, which is familiar in many respects to ethnographers of uniformed officers, but which also differed significantly. We contend that the organizing principle of surveillance – the imperative to maintain the secrecy of an operation – had a marked impact on our ethnographic experience, which eroded significantly our status as non-participant observers and altered out reflexive experience by activating the 'usefulness' of our gender.